Transanal Hemorrhoidal Dearterialization (THD) Anolift-Prospective Assessment of Safety and Efficacy - Giordano, Pasquale; Schembari, Elena (Frontiers in Surgery, 2021)
To facilitate the management of the prolapsing component the adjunct of a mucopexy to the conventional dearterialization has become a routine part of the THD procedure and has helped to expand the indications of this technique to more advanced stages of haemorrhoidal diseaseA simple technical modification of THD with targeted mucopexy (TM) called anolift is described. Aim of the study was to evaluate safety and effectiveness of this technical variation. The procedure consisted of two parts: one aimed at the dearterialization and the other concentrating on the management of the prolapsing component. Once all the arteries were identified and transfixed an anolift targeted mucopexy was performed using a continuous barbed suture with a synthetic absorbable monofilament (Polydioxanone) 2/0 Filbloc (Assut Europe) stitch mounted on a 4/8 30mm needle. Severity of haemorrhoidal symptoms was scored from 0 to 20 using a dedicated questionnaire (HASS). From May 2018 to November 2020, 60 patients with haemorrhoidal disease (HD) underwent a THD anolift procedure. Three patients experienced severe postoperative pain and ten (23%) suffered with difficulty in evacuation. The median follow-up period was 15.5 months (range 2-32 months). The mean HASS changed from 16.43 preoperatively to 1.95 postoperatively (p <0.0001). Preoperative HASS very strong correlated with the degree of haemorrhoids (p < 0.001), while there was no correlation between the preoperative HASS or the degree of haemorrhoids and the postoperative HASS (p = 0.163). There was no significant difference in predicted postoperative HASS according to the preoperative HD stage. One patient (1.6%) with circumferential IV haemorrhoids had a recurrence and required a further THD. Two patients had excision of skin tags (3%). The anolift technique is safe and effective for the management of HD even in patients with advanced stages.